Performance interfaces and destabilisation - Reeves, Stuart; Benford, Steve; O'Malley, Claire (2004)
Interaction with technology is occurring increasingly in public and semi-public settings and as a result the roles of spectator and performer are frequently being challenged by the deployment of computing systems. In this paper we discuss how the spectator, performer and interface feature in what we class as performance, how we might analyse their interrelation-ships and how traditional roles have become destabilised historically and technologically. In studying these relationships, we examine technological and non-technological examples from art, performance and exhibition design.